Use and abuse of humanism in international law - Anzaldi, Pablo Antonio (Estudios Internacionales, 2013)
This paper provides a critical view of the humanist ideology underlying NATO’s military actions. It distinguishes between both Kant’s and Hegel’s idealism and on that basis it suggests a distinction between the historical need for the advancement of law and the misuse of legal discourse. Finally, it points to the need of a new international law that considers the historic breakthrough of emerging nations.